The effect of permodified cyclodextrins encapsulation on the photophysical properties of a polyfluorene with randomly distributed electron-donor and rotaxane electron-acceptor units - Aurica Farcas; Ana-Maria Resmerita; Pierre-Henri Aubert; Flavian Farcas; Iuliana Stoica; Anton Airinei (Beilstein Journal of Organic Chemistry, 2014)
We report on the synthesis as well as the optical, electrochemical and morphological properties of two polyrotaxanes (4a and 4b), which consist of electron-accepting 9,9-dicyanomethylenefluorene 1 as an inclusion complex in persilylated β- or γ-cyclodextrin (TMS-β-CD, TMS-γ-CD) (1a, 1b) and methyltriphenylamine as an electron-donating molecule. They are statistically distributed into the conjugated chains of 9,9-dioctylfluorene 3 and compared with those of the corresponding non-rotaxane 4 counterpart. Rotaxane formation results in improvements of the solubility, the thermal stability, and the photophysical properties. Polyrotaxanes 4a and 4b exhibited slightly red-shifted absorption bands with respect to the non-rotaxane 4 counterpart. The fluorescence lifetimes of polyrotaxanes follow a mono-exponential decay with a value of τ = 1.14 ns compared with the non-rotaxane, where a bi-exponential decay composed of a main component with a relative short time of τ1 = 0.88 (57.08%) and a minor component with a longer lifetime of τ2 = 1.56 ns (42.92%) were determined. The optical and electrochemical band gaps (ΔEg) as well as the ionization potential and electronic affinity characterized by smaller values compared to the values of any of the constituents. AFM reveals that the film surface of 4a and 4b displays a granular morphology with a lower dispersity supported by a smaller roughness exponent compared with the non-rotaxane counterpart.